Aprendendo língua estrangeira a partir das contribuições dos jogos teatrais - Oliveira, Vênus Maély Garcia de (Universidade do Estado do Amazonas, 2020)
Written in first person, this work parts from a research-action to investigate the relation between the teaching and learning of foreign languages and theater in accordance to the theatrical games proposed by Viola Spolin, that, according to whom, enable experiencing, being fully involved and allows the learners of foreign languages (FL) to learn in a participative way, since of one the biggest difficulties that have been noticed in terms of learning is the lack of applicability of the contents in a real context. It is also sought to think the theatrical art in a conscious way as a methodology that comes from my pedagogic practices, conveying its effectiveness, assuming the junction of theater and LE. The research counts on the interdisciplinarity due to the search and partnership with professionals from the Arts field, that have been giving me a much needed orientation about aspects that have been unknown to me, for having only being graduated in Languages, thus providing the exchange of ideas to fulfill the expectations about artistic, pedagogic and aesthetic comprehension. In doing that, this work proposes thinking about teaching-learning as of reflections that instigate the different forms of teaching and, mainly, of learning, especially when there are theories that approach the multiple intelligences defended by Howard Gardner, also discussed in this work.